Review of the Adequacy of the Fund's Precautionary Balances. (Policy Papers; Policy Paper, 2018)
This paper reviews the adequacy of the Fund's precautionary balances, using the framework approved by the Board in 2010. The review takes place on the standard two-year cycle and assesses developments since the last review in 2016.